(untitled) (Research, Society and Development, 2022)
Objective: To characterize adverse events in an ICU in a public hospital. Methods: This is a quantitative, descriptive, retrospective study that analyzed admissions to the ICU in a public hospital between November and December 2019. The identification of adverse events occurred from the review of medical records. Statistical analysis using the MS Excel program, and considered the absolute and relative frequencies for categorical variables; and for continuous variables (mean, standard deviation, minimum and maximum), with the results presented in tables. There were 75 adverse events in 56.9% of 47 admissions. As for the harm to the patient, 38.7% were moderate AEs, 36% mild, 21.3% severe and 4% associated with death. Regarding the origin or type of event, the most frequent categories were: a) clinical process/procedure (56% of AEs), 28.6% of which were events with skin lesions, 21.4% related to procedures not performed, 19% events associated with the probe or drains, among others; b) clinical administration (13.3%), 70% of which were related to missed appointments; and c) infection (9.3%), with 57.1% related to bloodstream infection. Final Considerations: There is a high occurrence of adverse events in the studied ICU, which mainly caused moderate damage and are related to routine procedures in the sector, clinical administration and the control of hospital infections.